Three new 3, 4-seco-cycloartane triterpenoids from the flower of Gardenia jasminoides. (February 2018) - Zhang, Li-Sha; Wang, Yan-Lan; Liu, Qian; Zhou, Chang-Xin; Mo, Jian-Xia; Lin, Li-Gen; Gan, Li-She
Graphical abstract: Highlights: Three new 3, 4- seco -cycloartane triterpenoids (1–3) were isolated from the flower of Gardenia jasminoides . The chemical structures of new compounds were determined by 2D NMR and HRESIMS spectroscopic methods. Three isolates showed promising cytotoxic activity against HepG2 human hepatocellular carcinoma cell line. Compound 3 represented the first example of 3, 4-seco-cycloartane triterpenoid lactone with a oxygen-bearing C-1. Abstract: Three new 3, 4- seco -cycloartane triterpenoids (1 -3 ), including an unusual C-1 oxygenated 3, 4- seco -cycloartane triterpenoid lactone (3 ), along with six known triterpenoids, were isolated from 95% ethanol extract of the flower of Gardenia jasminoides . Their structures were determined by spectroscopic methods, especially 2D NMR and HRESIMS techniques. Compounds3, 4 ( dikamaliartane D), and7 (ursolic acid) showed promising cytotoxic activity against HepG2 human hepatocellular carcinoma cell line with IC50 values of 9.3, 27.7, and 39.3 μ M, respectively.